1981
DOI: 10.1002/cyto.990010502
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric probes of early events in cell activation

Abstract: By now, it's well established that the surface of a cell Contains transmembrane proteins which, on binding ligands, tell The biochemical computer inside what to do Without a need for any of the ligands coming through. Receptor‐triggered cytoplasmic “interrupt routines” May lead the nucleus to activate new sets of genes, Or otherwise induce a cell, which never reasons why, To twitch, secrete, endocytose, or reproduce, or die. By merely watching labeled ligands bind, we cannot know Down which of many paths the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Finally, we re-suspended the cells in 1·ml HBSS for fluorescence analysis. We acquired fluorescence emission intensity of 20·000 total counts (a count is any particle, such as a cell, that the flow cytometer detects) at 663·nm with a FACSCaliber flow cytometer (BD Bioscience, San Jose, CA; Johnson et al, 1980;Shapiro, 1981).…”
Section: Measurements Of Mitochondrial Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we re-suspended the cells in 1·ml HBSS for fluorescence analysis. We acquired fluorescence emission intensity of 20·000 total counts (a count is any particle, such as a cell, that the flow cytometer detects) at 663·nm with a FACSCaliber flow cytometer (BD Bioscience, San Jose, CA; Johnson et al, 1980;Shapiro, 1981).…”
Section: Measurements Of Mitochondrial Contentmentioning
confidence: 99%
“…In a novel approach, we examine two potential proximate correlates of variation in SMR, in addition to organ mass, in leopard frogs Rana pipiens. We measured SMR of the frogs, then measured the masses of energetically expensive organs, serum-free T4 thyroxine, and relative mitochondrial content using flow cytometry (Johnson et al, 1980;Shapiro, 1981). We asked three questions: first, how much amongindividual variation exists in the metabolic rate of an amphibian?…”
mentioning
confidence: 99%
“…Thus dye uptake by the cells is sensed indirectly by observing a fall in suspension emission. However, when cell fluorescences are measured individually by flow cytometry, there is no contribution from extracellular dye and it is therefore possible to detect cell uptake or release directly (Shapiro, 1981). In these circumstances it is undesirable to use a high concentration of dye, because 'saturation' of cell fluorescence would impede the detection of changes in cell dye content.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the fluorescent characteristics of nels 120-140) than did those comprised of more mature the cyanine dyes and selected applications in flow cytom-elements (areas 1 and 3). In addition, it is interesting to etry can be found in Shapiro et al (20)(21)(22) and Jacobber-note that the coefficient of variation ranges from 2.5 to ger (9,lO). Recently, Cohen et al (3) reported that the 5.0, and the mean channel number of the G1 peak also fluorescence intensity of fibroblasts exposed to cyanine varies from 97 to 101 between subpopulations, suggestwas dependent upon their cycling status.…”
Section: Discussionmentioning
confidence: 89%